2016
DOI: 10.1186/s13287-016-0324-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of long-term label-retaining cells in the regeneration of adult mouse kidney after ischemia/reperfusion injury

Abstract: BackgroundLabel-retaining cells (LRCs) have been recognized as rare stem and progenitor-like cells, but their complex biological features in renal repair at the cellular level have never been reported. This study was conducted to evaluate whether LRCs in kidney are indeed renal stem/progenitor cells and to delineate their potential role in kidney regeneration.MethodsWe utilized a long-term pulse chase of 5-bromo-2'-deoxyuridine (BrdU)-labeled cells in C57BL/6J mice to identify renal LRCs. We tracked the precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The composition of major epithelial cell types or BrdU-labeled cells in epithelium of a porcine lung was ascertained by following a standard histomorphometric analysis, recently set by the American Thoracic Society (ATS) [ 11 ]. Following the HE staining or immunohistochemistry staining on the serial transverse sections, epithelial cell counts were blindly made on every tenth section and then the cells with cell type-specific staining were counted by three senior technicians under a light microscope.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The composition of major epithelial cell types or BrdU-labeled cells in epithelium of a porcine lung was ascertained by following a standard histomorphometric analysis, recently set by the American Thoracic Society (ATS) [ 11 ]. Following the HE staining or immunohistochemistry staining on the serial transverse sections, epithelial cell counts were blindly made on every tenth section and then the cells with cell type-specific staining were counted by three senior technicians under a light microscope.…”
Section: Methodsmentioning
confidence: 99%
“…While the ciliated, secretory, and columnar cells constitute the primary host defense barrier, basal cells are a subpopulation of proliferating cuboidal-shaped cells that provide the major stem/progenitor cell function from which other airway epithelial cells are derived [ 5 9 ]. Submucosal glands (SMGs) in the airway are beneath the epithelium and restricted to the highest reaches of the cartilaginous region of airway, which have been demonstrated as the stem cell niche of the cartilaginous tracheal airway [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6c,d). In addition, we analyzed whether the proliferating cells were tubular or interstitial cells on day 3, which is the point when cell proliferation is considered the most increased after IRI 39,40 . When the number of EdU-positive cells was evaluated by dividing the cells into tubular and interstitial cells, the proliferative capacity with regard to both tubular and interstitial cells was significantly lower in cKO mice than in control mice, and the difference was especially prominent for renal tubular cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the replacement cells ultimately form normal epithelial cells 48 . Some reports have mentioned that peak cell proliferative capacity is noted 3–4 days after IRI 39,40 . Consistent with the results of previous reports, our results indicate that cell proliferation in control mice increased on day 3 rather than on day 1 after IRI.…”
Section: Discussionmentioning
confidence: 99%